Nursing care for children diagnosed with Autism Spectrum Disorder (ASD) (Research, Society and Development, 2025)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition that affects communication, social interaction, and behavior, with manifestations generally identified in early childhood. The complexity of the condition requires a multidisciplinary approach, where nursing care stands out as fundamental to promoting child development, well-being, and autonomy, respecting their individual characteristics. Objective: To analyze the healthcare demands of children diagnosed with Autism Spectrum Disorder (ASD), identifying the main challenges faced by healthcare professionals in caring for this population, the barriers to accessing specialized services, and the strategies used to improve the quality of care. Methodology: This is an integrative literature review. The search was conducted in the LILACS, SciELO, and BDENF databases, using the combination of the descriptors "Autism Spectrum Disorder" and "Healthcare". The search period encompassed publications between 2019 and 2025. Results: The results allowed for the systematization of information on the most critical aspects of healthcare, such as: the need for interdisciplinary approaches, gaps in professional training, communication difficulties, and the management of health conditions associated with ASD. These findings provide support for the implementation of evidence-based practices. Conclusion: The research contributed to the improvement of care practices, benefiting not only children with ASD, but also their families, who play an essential role in the continuity of interventions.